Improving Student Competencies Through Work-Based Learning Model Group Investigation in Vocational Education - Taufiq Nur Muftiyanto; Muhammad Akhyar; Munawir Yusuf; Sri Haryati (Jurnal Pendidikan Indonesia, 2021)
This study aimed to analyze the conditions of learning in Diploma III vocational education and the influence of the Group Investigation-based Work-Based Learning model on nursing diploma III vocational education. This type of research is a type of qualitative research. This research describes or describes an actual problem, and from these results, it can be concluded or generalized. This research approach is a descriptive approach, which is an approach that aims to make systematic, accurate, and factual descriptions of populations and certain objects. The population of this study was students of nursing Diploma III vocational education. The data collection technique was carried out by observing learning, then followed by interviews. Data analysis in qualitative descriptive research is a gradual progression flow, assigning informants to writing reports. After going through observations and interviews, the study results indicate that applying the Work-Based Learning and Group Investigation models is very relevant in implementing nursing vocational education and positively influences student competency abilities. This finding will have implications to improve students' competence in vocational education. The Work-Based Learning model based on Group Investigation can create a learning atmosphere in vocational education.